2008
DOI: 10.1183/09031936.00020607
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics of patients with extrapulmonary tuberculosis in Germany

Abstract: The aim of the present study was to determine the demographics of patients with extrapulmonary tuberculosis in Germany.Data on 26,302 tuberculosis cases from a national survey carried out during the period 1996-2000 were analysed.The crude proportion of tuberculosis patients with extrapulmonary manifestations was 21.6%. Extrapulmonary tuberculosis was most likely among females, children aged ,15 yrs and persons originating from Africa and Asia. Females tended to be more likely to have any form of extrapulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
101
6
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(143 citation statements)
references
References 26 publications
25
101
6
7
Order By: Relevance
“…The association between sex and having EPTB alone is consistent with the findings from previous studies. 5,6,16,26 However, our observation that females had a significantly decreased likelihood of having EPTB plus PTB is new. The observed different effects of sex on having EPTB alone and having EPTB plus PTB are intriguing and warrant further investigations to gain a better understanding of the reasons for the observed variation in the sex effect between EPTB alone and EPTB plus PTB.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…The association between sex and having EPTB alone is consistent with the findings from previous studies. 5,6,16,26 However, our observation that females had a significantly decreased likelihood of having EPTB plus PTB is new. The observed different effects of sex on having EPTB alone and having EPTB plus PTB are intriguing and warrant further investigations to gain a better understanding of the reasons for the observed variation in the sex effect between EPTB alone and EPTB plus PTB.…”
Section: Discussioncontrasting
confidence: 39%
“…EPTB was found to account for 21.6%, 27%, and 38% of all TB cases in studies conducted in Germany, 26 the United States, 6 and The Netherlands, respectively. 7 In these studies, the proportions of immigrants were 32.1%, 43% and > 50%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is seen in children with a lower frequency. Recently, Forssbohm et al [6] reported that in Germany, only 5% of peritoneal TB cases were children under 14 years old. In the US, peritoneal TB accounts 0.3% of all TB cases in children less than 20 years and median age in children was 13 years [7] .…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO, the Eastern Mediterranean region shows the highest incidence of EPTB in the world [1]. One possible assumption is that this high rate may related to the high probability of reactivation of latent infection, particularly among migrantreceiving countries [15]. On the other hand, another unexplored possibility is related to the host genetic factors, as all the Arab counties are prone to genetic disorders and related complications mainly because of the high rate of consanguinity.…”
Section: Pulmonary Tb and Extrapulmonary Tbmentioning
confidence: 99%